Aplicativo de nutrição para idosos em cuidados paliativos - Moura, Raquel Bezerra Barbosa de (2022)
Introduction: The accelerated aging of the population collaborates with the increased incidence of chronic non-communicable diseases that can lead to a reduction in the functional capacity of the elderly, leading to the need for palliative care. The nutritionist is an important member of the multiprofessional team in the care of the elderly person in palliative care, acting in the management of symptoms and improving the quality of life of this population, being of utmost relevance to spread the knowledge about the nutritional interventions directed to the elderly person in palliative care. Objectives: To identify the main nutritional interventions for the elderly in palliative care; to elaborate a protocol with the nutritional interventions identified; to validate the protocol by expert judges; to propose and validate an application with nutritional interventions for the elderly in palliative care. Method: This is a methodological study conducted in four stages. The first stage consisted of a scope review to identify the main nutritional interventions for the elderly in palliative care; in the second stage, a protocol of nutritional interventions for the elderly in palliative care was constructed; in the third stage, the protocol was validated by expert judges; finally, in the fourth stage, an application with nutritional interventions for the elderly in palliative care was developed and validated. Results and Discussion: The following were produced: 1- A review article with the scope "Nutritional interventions for the elderly in palliative care", whose findings identified interventions focused on quality of life, symptom management and improvement of nutritional status. 2- A protocol resulting from the scoping review research, also considering recommendations from guides for protocol development; government publications; and scientific studies in common with the topic. Validation was performed by 6 expert judges, through 23 items distributed in 6 domains, and two items of general classification, described in the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument. 3- Based on the validated protocol, an application named NutriCP was developed, directed to nutritionists who work with palliative care elderly patients, and validated by 13 expert judges using the content validation method (CVI). Final considerations: The scoping review identified the nutritional interventions adopted in the elderly in palliative care, which mostly comprise: nutritional counseling, oral nutritional supplementation and artificial nutrition by means of enteral and parenteral nutrition. The validation of the protocol and application content by expert judges provided greater reliability in the development of the products of this dissertation, the protocol and the application, highlighting the importance of its content to optimize the conduct of the nutritionist regarding the best strategies of nutritional interventions for the elderly in palliative care, promoting relief to their suffering, comfort, well-being and consequently, better quality of life.